POSSIBILITIES AND CHALLENGES OF AGRICULTURAL CULTURE EDUCATION IN SHORT STORIES - Gowda, Harisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Harmony between the educated and the uneducated among farmers: In the story “Muttu”, the difficulties of harmony between the life of a farming family and those who have gone to Bangalore city to get an education and work are expressed through the experiences of the village and the city dwellers. The heroine of this story, “Nimmi”, says, “I have felt a thousand times that I could have married a landlord and become a gardener. It is only a feeling, but the infatuation of the magical city of Bangalore leaves no one. There is a crazy desire to cut down something here, build a fence and save it. What is being achieved is nothing, only the necessities of food and clothing for two days.